PENGARUH AKUNTABILITAS, TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN,DAN KOMITMENMANAJEMEN TERHADAP PENERAPANTRANSPARANSI PELAPORANKEUANGAN (STUDI EMPIRIS PADA SKPD KABUPATEN INDRAGIRI HULU) - M. Arif Syarmenda; M. Rasuli '; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The transparency of financial reporting requires that the organization to present the financial statements are free of material false and biased information to outside parties. This is in accordance with the concept of reliability of the information in the financial statments to be free of errors and misleading understanding of the material, presenting any facts honestly, and can be verified. Transparency can be affected by accountability, external pressure, the uncertainty of the environment, and management commitment. This research was conducted in the city with the object of research is the Indragiri Hulu department, agencies, and offices in Indragiri Hulu by 28 workers work unit of local government. Samples taken in this study were 84 respondents. Data collection is carried out using a questionnaire which is then analyzed using linear regression. Test results showed accountability influence significant .037 ,external pressure .004, the uncertainty of the environment .002, and management commitment .015. Influence of the application of the transparency of financial reporting in the goverment of Indragiri Hulu. The magnitude of the influence accountability external pressure, the uncertainty of the environment, and management commitment for the implementation of govermental financial reporting transperency Indragiri Hulu was 50,2 %.Keywords : Accountability, External Pressure, Environmental Uncertainty, Commitment, Transparancy and Financial report